PkM Peningkatan Kemampuan Masyarakat Desa Terhadap Teknologi Informasi melalui Jaringan Internet Sebagai Penerapan IoT Desa Cerdas - M . Syafiih; Nadiyah Nadiyah; Matlubur Khairi; M Fadhilur Rahman; Muafi Muafi (Universitas Nurul Jadid, 2023)
Bucor Wetan Village is one of the villages in Pakuniran District, Probolinggo Regency, a village with a strong cultural culture and a religious community that makes villagers have a very high level of awareness of education. Such conditions are not matched by balanced infrastructure development, including uneven and unstable internet services. From these problems, the service team will provide training and assistance to improve the ability of the community to be able to build an internet network so that all residents will enjoy a stable internet network, the output of this activity will make the village smart with the ability to use information technology. he The method used with assistance starts planning, implementation, and evaluation. The results of community service have made the residents of Bucor Wetan Village have the ability to build an internet network and enjoy a stable internet.